The Role of the Medial Habenula Cholinergic System in Addiction and Emotion-Associated Behaviors - Lee, Hyun Woo; Yang, Soo Hyun; Kim, Jin Yong; Kim, Hyun (Frontiers in Psychiatry, 2019)
The habenula is a complex nucleus composed of lateral and medial subnuclei, which connect between the limbic forebrain and midbrain. Over the past few years, the lateral habenula has received considerable attention because of its potential roles in cognition and in the pathogenesis of various psychiatric disorders. Unlike extensively studied lateral habenula, anatomically and histologically distinct medial habenula remains largely understudied. The medial habenula can be further subdivided into a dorsal region containing excitatory neurons that express the tachykinin neuropeptide substance P and a ventral region containing dense cholinergic neurons. Although the medial habenula is the source of one of the major cholinergic pathways in the brain, relatively few studies have been conducted to understand its roles. Recently, however, the medial habenula cholinergic system has attracted more attention because of its potential to provide therapeutic targets for the treatment of nicotine withdrawal symptoms, drug addiction, and various mood disorders. Here, we discuss the role of the medial habenula cholinergic system in brain function.